Initiatives on Education Diplomacy/Linkages: The Chequered Experience in Nigeria - Nyewusira, Benjamin N.; Nyewusira, Chituru; Nwaogu, Okechukwu Akara (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The study provided clear indications from the studies of comparative education that Nigeria’s educational system is not highly rated when compared to many other educational systems around the globe. Research evidences are also rife on the use of education diplomacy and international linkages for bridging the gaps of educational inequalities between developed and developing nations. Methodology: As a qualitative study, the paper adopted historical research design, relying on documentary analysis to establish the tenets of education diplomacy/ linkages are not only capable of improving Nigeria’s educational system, but can equally be used to elevate it to a point of global relevance and reference. Main Findings: Revealed in the study are the four major purposive initiatives that are corollaries of education diplomacy/ linkages are depicted in the praxes associated with Foreign Aid packages, Technical Aids Corps, Foreign Studentship schemes and Internalization programme in higher education. The treatise critical appraises the exploration and use of these initiatives for educational image-making and cautious integration of the country’s educational system with global best practices. Despite the chequered experiences identifiable with the initiatives, the inherent derivatives of these initiatives are extremely gainful to the overall development of education in Nigeria. Novelty/Originality of this study: Finally, the paper strongly advocated that Nigeria needs to carefully re-engage and follow through the gains in these initiatives, so as to unlock and tap from the intrinsic benefits and humongous opportunities derivable from the thrusts of education diplomacy linkages.